Pengaruh Model Project Based Learning (PjBL) Diorama Dalam Pembelajaran IPA Terhadap Kemampuan Berpikir Kreatif Siswa Kelas IV Sekolah Dasar - Dayana, Resi; Winarni, Endang Widi; Agusdianita, Neza (Universitas Bengkulu, 2021)
This study aims to determine the of tge PjBL learning model, Diorama in science learning on the creative thinking abilities of fourth grade students in elementary schools. This research is a wuantitative research. The method used is quasy experiment. The design in this study is The Matching Only Pretest-Posttest control Group Desigen. The population in this study were all students in Elementary School Cluster X Bengkulu City. The samples in this study were students of class IV A SDN 58 Bengkulu City, amounting to 20 people as experimental clasa and class IV B stduents of SDN 38 Bengkulu City, totaling 21 people as control class. The instrument used in the form of multiple choice tests consisted of dimensions of flency, flexible thingking, original thinking, elaboration, and thinking ability to evaluate (evaluation) provided through pretest and posttest. This research also resulted in a Diorama Project that affected students’ creative thingking abilities. The data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics. Based on the results of this study note that the ?????? of 2.58 greater that ?????? at a significant of 5% of 2.02. This shows that threre is an influence of the Diorama Project Based Learning (PjBL) model in natural science learning on the creative thinking abilities of grade IV elementary school students.Keywords : Project Based Learning (PjBL) Leraning Model, Thinking Creative